IT Strategies in Government Policies:A Case Study of M.P.(Part-I) - Sharma, Pratibha (International Journal of Computer Sciences and Engineering, 2025)
Through this paper we have representation of the IT strategies that were in effect from previous decade; these all strategies got frequent changes as demanded by time to give more effective, impressive and accurate services to the state’s people from various government organizations of states. These organization of state are putting their effort positively to place state on growing track through which state could achieve goal of smarter state of India that could make its name in whole world by their more positive effort with new IT models by which all cities and villages of state would be smarter by their effective, secure and paper less working technique with new IT concepts, Madhya Pradesh (M.P.) are the state that are enlighten itself by their more impressive and positive effort to achieve that great goal with new IT strategies. These all strategies help state to free it from crime and unemployment. These all also help to provide smart education, smart health care system, smart electricity supply etc.